Long COVID in Brazilian healthcare workers: Case-control study on physical and mental health outcomes in northeastern Brazil - Barbosa, Danielly Alves Mendes; da Conceição, Ewerton Henrique; Santos, Maria Renata da Silva; Maior, Caio Souto; Didier, Isis Lins; Araujo, Alice Valença; Gomes, Ana Lisa do Vale (Acta Biomedica Atenei Parmensis, 2025)
Long COVID syndrome causes a variety of neurocognitive, respiratory, and cardiac symptoms, which can be persistent and debilitating, which result in significant impacts on quality of life in terms of mental and physical health. In this work, we conducted a case-control study with 53 healthcare workers. The investigation of Long COVID was carried out with the ONS questionnaire and the assessment of quality of life and physical and neuropsychological health with the PROMIS Global 10 questionnaire. Notably, 66.7% of individuals with intense impact on quality of life belonged to the low physical health score group, while 40% belonged to the low mental health group. Out of 53 subjects, 26 were identified with Long Covid, where 7% had a reduction in their mental health score, and the impact on quality of life was intense for 14 and moderate for 11 of them. These results indicate that prolonged Long COVID symptoms have a substantial effect on the quality of life of patients, especially those with low levels of physical and mental health. The study identified significant impacts between intense and moderate on the physical and psychological health of the healthcare professionals studied, highlighting the association with those who had a loss of smell and taste during the acute phase of the infection.